Evaluation of Telehealth Services that are Clinically Appropriate for Reimbursement in the US Medicaid Population: Mixed Methods Study - Sanjeev Saravanakumar; Andrey Ostrovsky (JMIR Publications, 2024)
BackgroundWhen the US Department of Health and Human Services instituted a State of Public Health Emergency (PHE) during the COVID-19 pandemic, many telehealth flexibilities were fast-tracked to allow state Medicaid agencies to reimburse new specialty services, sites of care, and mediums such as FaceTime to communicate with patients.. This resulted in expanded access to care for financially vulnerable Medicaid patients, as evidenced by an uptick in telehealth use. Research has mostly focused on telehealth reimbursement for limited use cases such as rural primary care, without broader consideration for how telehealth can be appropriately mainstreamed and maintained. ObjectiveThis study sought to (1) evaluate the continuation of flexible telehealth reimbursement broadly, beyond the COVID-19 pandemic; (2) analyze the clinical effectiveness of the new telehealth services; and (3) offer code-by-code reimbursement guidance to state Medicaid leaders. MethodsWe surveyed 10 state Medicaid medical directors (MMDs) who are responsible for the scientific and clinical appropriateness of Medicaid policies in their respective states. Participants were asked to complete an internet-based survey with a list of medical billing codes, grouped by service type, and asked if they believed they should be reimbursed by Medicaid on a permanent basis. Additional questions covered more detailed recommendations, such as reimbursing video with audio versus audio-only, guardrails for certain specialty services, and motivations behind responses. ResultsThe MMDs felt that the majority of services should be reimbursed via some modality of telehealth after the PHE, with the most support for video combined with audio compared to audio-only. There were exceptions on both ends of the spectrum, where services such as pulmonary diagnostics were not recommended to be reimbursed in any form and services such as psychotherapy for mental health had the most support for audio-only. The vast majority of MMDs were supportive of reimbursement for remote monitoring services, but some preferred to have some reimbursement guardrails. We found that 90% (n=9) of MMDs were supportive of reimbursement for telehealth interprofessional services, while half (n=5) of the respondents felt that there should be continued guardrails for reimbursement. Motivations for continuing reimbursement flexibility were largely attributed to improving access to care, improving outcomes, and improving equity among the Medicaid patient population. ConclusionsThere is a strong clinical endorsement to continue the telehealth flexibility enabled by the PHE, primarily for video combined with audio telehealth, with caution against audio-only telehealth in situations where hands-on intervention is necessary for diagnosis or treatment. There is also support for reimbursing remote monitoring services and telehealth interprofessional services, albeit with guardrails. These results are primarily from a perspective of improving access, outcomes, and equity; other state-specific factors such as fiscal impact and technical implementation may need to be taken into account when considering reimbursement decisions on telehealth.